Impulsive buying from an Islamic perspective: The role of price discounts, brand image, and product quality in thrift product purchases - Siregar, Mirza; Nurlaila, Nurlaila; Aisyah, Siti (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This study aims to analyze the influence of price discounts, brand image, and product quality on impulsive buying behavior of thrift products (branded second-hand goods) in the Asam Kumbang area, Medan, from an Islamic perspective. In Islam, consumption behavior is guided by the principles of balance (wasatiyyah), benefit (maslahah), and the prohibition of extravagance (israf). This research employs a quantitative approach with data collected through questionnaires. The findings reveal that marketing strategies such as price discounts, brand image, and product quality can encourage impulsive buying, which, from an Islamic perspective, should be approached with caution. Consumers are advised to prioritize genuine needs and consider sustainability and blessings (barakah) in every purchasing decision. Public interest statements This study aims to analyze the influence of price discounts, brand image, and product quality on impulsive buying behavior for thrift products in Asam Kumbang, Medan. From an Islamic perspective, purchases should align with Sharia, avoiding wastefulness (israf) and promoting halal benefits. Findings encourage balanced marketing strategies supporting ethical and efficient consumer decisions.